70 Caribbean recipes: taste sensations from the tropics - Grant, Rosamund; Grant, Rosamund (London, 2007)
A Taste of the Caribbean features recipes that reflect the rich diversity of traditions and culture that is the hallmark of the Caribbean. People of many different races and cultures have lived in the Caribbean islands over the cen-turies, and their presence changed not only the history of the islands, but also profoundly influenced its cuisine. With each set of people came their traditional cooking methods, they imported their own favourite foods, planting fruit and vegetables and rearing livestock. Gradually over the years the various islanders embraced these traditions as their own and today we have to realise that what we think of as Caribbean cooking, is actually a blend of food and cookery traditions from all over the world.
Keywords: Cooking african; Cooking caribbean